2021
DOI: 10.21203/rs.3.rs-1016584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of mass vaccination on SARS-CoV-2 infections among the total multiple sclerosis population receiving immunomodulatory disease-modifying therapies in England

Abstract: This study aimed to understand changes in the risk of SARS-CoV-2 infection among all people with multiple sclerosis (MS) receiving immunomodulatory disease-modifying therapies (DMTs) in England, compared to the general population, following mass vaccination. Longitudinal data collected by the National Health Service (NHS) England on all MS DMT prescriptions and the UK Health Security Agency on all registered SARS-CoV-2 test results were analysed. The incidence rate ratio of SARS-CoV-2 infection among people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This result is supported by a recent study from England that compared the incidence risk ratio of SARS-CoV-2 infection between MS patients and the general population before and after mass vaccination. They found an increase in infection risk in MS patients treated with ocrelizumab, as an anti-CD20 agent, compared to the general population after vaccination [ 14 ]. A multi-center retrospective study from Italy showed a higher rate of SARS-CoV-2 mRNA Vaccine breakthrough infection in fully vaccinated MS patients on ocrelizumab and fingolimod than in patients treated with other DMTs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is supported by a recent study from England that compared the incidence risk ratio of SARS-CoV-2 infection between MS patients and the general population before and after mass vaccination. They found an increase in infection risk in MS patients treated with ocrelizumab, as an anti-CD20 agent, compared to the general population after vaccination [ 14 ]. A multi-center retrospective study from Italy showed a higher rate of SARS-CoV-2 mRNA Vaccine breakthrough infection in fully vaccinated MS patients on ocrelizumab and fingolimod than in patients treated with other DMTs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%